Model Evaluasi Dalam Implementasi Kebijakan Car Free Night Untuk Penguatan Kapasitas Pariwisata di Kota Palembang - Madani, K.M. Isnaini; Sriati, Sriati; Nadjib, Abdul; Alfitri, Alfitri (Universitas Medan Area, 2025)
This study aims to analyze the implementation of the Car Free Night policy in Sekanak Lambidaro as an effort to strengthen the tourism capacity of Palembang City, as well as formulate a policy evaluation model based on collaborative governance. The research method uses a qualitative approach with a case study design. Data were obtained through in-depth interviews, participatory observations, and document review, with informants selected using purposive sampling techniques. The results of the study show that Car Free Night has the potential to become a leading night tourism icon because it is able to attract visitors, increase MSME turnover, and strengthen the image of the destination. However, its sustainability is still constrained by unclear operational regulations, budget limitations, supporting infrastructure, and suboptimal cross-sector coordination. The proposed evaluation model integrates quantitative and qualitative indicators, division of roles in data collection, and transparent reporting of evaluation results. The collaborative governance approach is believed to be able to strengthen the participation of all stakeholders, increase policy effectiveness, and support sustainable tourism development in the city of Palembang.